AITAB contract: implementation of moratorium at Islamic banking institutions during COVID-19 / Nur Ain Nazihah Muhammad Rizal ... [et al.] - Muhammad Rizal, Nur Ain Nazihah; Abd Mutalib, Hasyeilla; Mohammed Noor, Afiffudin; Gzahli, Nurnazifa; Abd Rahman, Nur Athirah (Universiti Teknologi MARA, Perlis, 2024)
The implementation of the moratorium during the COVID-19 pandemic has caused negative reactions to Islamic banking institutions. Therefore, this study has analysed the implementation of the moratorium in Islamic banking institutions in relation to AITAB contracts during COVID-19. This study uses a qualitative method by interviewing two respondents from the same local Islamic banking institution. The data were then subjected to thematic analysis. According to the research findings obtained from IM1 and IM2, the implementation of the first phase moratorium is carried out automatically, and the implementation of the second phase moratorium is carried out in a targeted manner, along with the rescheduling of the AITAB contract. Findings from this study will provide exposure to customers regarding the implementation of the moratorium during the COVID-19 pandemic on AITAB contracts. However, this study only focuses on the AITAB contracts which implemented by the Islamic banking institutions.